Pengaruh Kecerdasan Buatan (AI) dalam Optimalisasi Manajemen Pemasaran Digital pada UMKM di Era Ekonomi Kreatif - Dayuni, Dayuni (Fakultas Ekonomi Universitas Gresik, 2025)
The development of artificial intelligence (AI) technology has presented strategic opportunities for micro, small, and medium enterprises (MSMEs) to increase their competitiveness in the increasingly competitive creative economy era. However, the adoption of AI in MSMEs still faces various obstacles, such as limited digital literacy and implementation costs, so a more in-depth empirical study is needed. This study aims to analyze the effect of AI utilization on optimizing MSME digital marketing management, particularly in improving the effectiveness of marketing strategies and business performance. The research method used is a quantitative approach with a survey of 120 MSMEs in the creative economy sector in Indonesia. Data were collected through a Likert-scale-based questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that AI utilization has a significant effect on digital marketing strategies (β = 0.61; p < 0.001) and marketing performance (β = 0.48; p < 0.01), with digital strategies proven to mediate the relationship between AI and marketing performance (β = 0.55; p < 0.001). MSMEs with high AI adoption experienced an average sales increase of 21.7% in the last six months, higher than MSMEs with low adoption (9.1%). The implications of this study emphasize the importance of public policy support, increased digital literacy, and the development of an affordable technology ecosystem to strengthen MSMEs' digital transformation and increase their competitiveness in the global market.